"The doctor said formula would help me": Health sector influences on use of infant formula in peri-urban Lima, Peru. (January 2020) - Rothstein, Jessica D.; Caulfield, Laura E.; Broaddus-Shea, Elena T.; Muschelli, John; Gilman, Robert H.; Winch, Peter J.
Highlights: Describes rates of unnecessary formula use during infants' first 60 days of life. Demonstrates how formula companies market products directly to health providers. Reveals how providers' formula "prescriptions" lead to higher mixed feeding rates. Describes how poor counseling from nurses hinders mothers' ability to breastfeed. Shows the need to improve monitoring of legislation to control formula marketing.